Optimization of hard disk drive motor for better acoustical performance - Yap, Chee Wee. (2010)
In this project, a Cheetah Entreprise 3.5’’ Hark Disk Drive(HDD) is tested in the Anechoic Chamber to find out the noises generated by the spindle motor at different speed. The sound power level and sound pressure level are measured and calculated by using the software Bruel & Kjaer – PULSE Labshop Version 14.0.0. The sound pressure FFT results are obtained and a computer simulation is done by using ANSYS and SYSNOISE.